Can institutionalized adolescent females with a substantiated history of sexual abuse benefit from cognitive behavioral treatment targeting disruptive and delinquent behaviors? - Vugt, Eveline van (Criminal justice and behavior, 2016)
The present study examined to what extent adolescent females in residential care with a substantiated history of sexual abuse can benefit from a cognitive behavioral treatment (CBT) targeting disruptive and delinquent behaviors. In total, 104 adolescent females in the treatment group and 78 adolescent females in the comparison group were included in the evaluative design. Latent growth models (LGM) were performed to model change in adolescent females? conduct and anger problems. In the short term, 3 months after the treatment, adolescent females with sexual abuse experiences receiving CBT showed stronger declines in trait anger and anger expression compared with the other groups. Furthermore, in the long term, 18 months after admission, this group of females showed larger declines in proclivity for trading sex compared with the other groups. Results are discussed in the light of the ?what works? literature for effective interventions.